Attitudes and motivation towards learning English as a second language of Rembau MARA Higher Technical College undergraduates / Salwa Othman - Othman, Salwa (2015)
Attitudes and motivations have always been investigated among numerous researchers in the area of learning English as a second language learning. This is mainly because they are believed to influence the process of acquiring the second language learning. Hence, this study was carried out with the aims to investigate the attitudes and motivations, and their relationship towards learning English as a second language of Rembau MARA Higher Technical College undergraduates. Generally, a mixed-methods research design consisting of both quantitative and qualitative approaches was employed in order to explore the variables. Stratified random sampling procedure was used to select a total of 130 undergraduates at Rembau Higher Technical College as respondents of the study. The quantitative data was collected using an integrated Attitude and Motivation Test Battery (AMTB) instrumentation developed by Gardner (2004). A set of questionnaire with a six-point Likert scale was used to measure 56 items on attitudes and motivations variables. In addition, qualitative data was collected using six open-ended questions posted to the respondents via the same questionnaire. Findings revealed that firstly, the Rembau MARA Higher Technical College undergraduates had positive attitudes (M = 4.76) and high motivations (M = 4.50) towards learning English as a second language. Secondly, the one-way ANOVA statistical test showed that there was a significant difference of attitudes among undergraduates according to their academic performances at the p <.05 level [F (3, 126) = 6.28, p = .001]. Thirdly, there was a significant difference of motivations among undergraduates according to their academic performances at the p <.05 level [F (3, 126) = 4.15, p = .008], Fourthly, there was a significant difference of attitudes between the male (M= 4.61) and female (M = 4.97) undergraduates. Fifthly, there was a significant difference of motivations between the male (M = 4.34) and female (M = 4.72) undergraduates. Sixthly, the Pearson product moment correlation coefficient analysis revealed a moderate and positive correlation (r = .74) between attitudes and motivations. Lastly, qualitative findings seemed to triangulate and support the quantitative findings. Majority of the undergraduates agreed that positive attitudes and high motivations tend to influence them to be more enthusiastic and committed in learning English as a second language. Justifications for being positive and negative attitudes and motivations were also recorded from the respondents. In short, all these lead to important implications and recommendations for the future study.